PENGARUH LATIHAN IMAJINASI(IMAGERY) VISUAL TERHADAP KETERAMPILAN MENYERANG GYAKU TSUKI PADA SISWA EKSKUL KARATE SEKOLAH MENENGAH PERTAMA NEGERI 7 BEKASI - Yunita Suprapti; Eva Julianti; Fahmy Fahrezzy (Jurnal Pendidikan Jasmani dan Adaptif (JPJA), 2018)
The purpose of this study is to determine whether there is an influence on the skills of attacking gyaku tsuki through visual imagery exercises (visual imagery) on karate sports. This research is using experimental method. The data were collected using observation guidance instrument and analyzed by qualitative descriptive. Sample used as many as 12 students. This study used 8 meetings. It can be concluded that the result of the research is the influence of visual imagery imagination exercise on the skills of attacking gsaku tsuki on the junior high school students of the state 7 bekasi, with data obtained t-count (9,386)> t- table (1,796) then H0 rejected. So it can be concluded that proven visual imagination (imagery) exercise can improve the skills of attacking gyaku tsuki on karate extracurricular of the junior high school students of the state 7 Bekasi.